Foraminifera occurrences of IODP Hole 386-M0084C - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Results of Foraminifera assemblage analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the offshore phase, micropaleontology samples were taken from the end of split cores at 5 m intervals. During the onshore phase approximately 2 cubic centimetres of sediment from each of these samples were analysed for foraminifera. After drying overnight in a ~40°C oven, samples were disaggregated in a solution of deionized water, Calgon, and H2O2 to ensure removal of clay-sized particles. Samples were then wet sieved through a 63 μm mesh sieve and rinsed with deionized water. The coarse fraction was placed on filter paper in an oven at ~40°C until it dried completely. Faunal identifications were made using a Meiji Techno RZ binocular light microscope. Taxonomic composition, abundance, and preservation state were observed in the >63 μm size fraction. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023